Value chain analysis of Chaya (Mayan Spinach) in Guatemala - Amaya, N.; Padulosi, S.; Meldrum, G. (Springer, 2020)
Chaya is a highly nutritious perennial leafy vegetable native to Mesoamerica. This drought-resistant crop has low production and consumption levels in Guatemala, but has the potential to help agriculture and food systems be more nutritious and resilient. This study analyzed the value chain of chaya in Guatemala, and identified bottlenecks and opportunities for its use-enhancement. This research, the first of its kind applied to this crop in Guatemala, combined Rapid Market Appraisal tools. Small-scale chaya production, consumption, and marketing were observed in three focal sites (Guatemala City, Petén, and Dry Corridor). It was observed that producers are not motivated to produce chaya commercially and vendors are unwilling to sell it because of low demand and profitability. One Guatemalan company identified produces nutraceutical chaya products with few sales points in the country and occasionally abroad. Low demand is a primary bottleneck in the value chain due to lack of consumer awareness, changing eating habits, limited recipes, and availability in home-gardens. There is also a reluctance to grow, consume, or sell a crop perceived as a “food of the poor.” Low prices and profitability were other constraints registered. The findings can inform future interventions for enhancing the use of this crop to fight malnutrition.